2020
DOI: 10.1080/09540121.2020.1845289
|View full text |Cite
|
Sign up to set email alerts
|

Power to participants: methodological and ethical reflections from a decade of adolescent advisory groups in South Africa

Abstract: Whilst the HIV response has made significant progress in increasing representation of adults affected by HIV, the meaningful inclusion of children and adolescents has lagged. But this may be a pivotal moment of change. We report on a decade of conducting adolescent advisory groups in South Africa, to reflect on youth advisory processes. Data was collected from 2008 to 2018 from adolescent advisors (n = 60) and researchers (n = 25), and included feedback sessions, social media, anonymous "post-boxes" and interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 25 publications
(26 reference statements)
0
35
0
Order By: Relevance
“…We consulted prior to baseline with local traditional leaders, local provincial government, pre-piloted with adolescents from these population groups, and introduced the study at multiple community meetings. The design of the study and questionnaire was carried out in consultation with our South African Teen Advisory Group [12].…”
Section: Methodsmentioning
confidence: 99%
“…We consulted prior to baseline with local traditional leaders, local provincial government, pre-piloted with adolescents from these population groups, and introduced the study at multiple community meetings. The design of the study and questionnaire was carried out in consultation with our South African Teen Advisory Group [12].…”
Section: Methodsmentioning
confidence: 99%
“…A recent review of experience of youth involvement, particularly in research activities in South Africa, provides useful lessons for a future short courses and programming. 8 …”
Section: Discussionmentioning
confidence: 99%
“…The AYHP has demonstrated that youth participation is possible through long standing research partnerships and is a foundation on which to build and contextualise youth as expert actors, as a more proactive approach to youth engagement in policy processes and programmes. As documented by Cluver et al 73 participatory research approaches, such as youth participatory action research, photo-voice, and digital modes, can acknowledge and attempt to address the power imbalances that privilege researchers and adult perspectives and agendas, as well as challenge top-down policy development. [74][75][76][77][78][79] However, it is also important to be aware of the relevant methodological, pedagogical approaches as well as tensions, power relations and potential resistance by policy-makers and other actors.…”
Section: Positioning and Research Processesmentioning
confidence: 99%